2021
DOI: 10.1182/blood-2021-152769
|View full text |Cite
|
Sign up to set email alerts
|

Results of Hematopoietic Stem Cells Transplantation with Tcrαβ and CD19-Depletion from Matched Related Donors and Infusions of CD45RA Depleted Donor Lymphocytes in Pediatric Severe Aplastic Anemia

Abstract: Introduction HSCT from matched family donors results in most favorable outcomes among children with severe aplastic anemia (SAA). Despite overall success, morbidity, associated with acute and chronic graft-versus-host disease (GVHD) is not completely prevented with current standard of pharmacologic prophylaxis. Depletion of ab T cells from the graft prevents GVHD, and improves outcome of hematopoietic stem cell transplantation from haploidentical donors, while infusions of donor memory lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The use of CD45RA-depleted T cells has also been studied in other transplantation protocols. 32 , 33 , 34 In a randomized trial of TCRαβ-depleted allogeneic HSCT, post-transplant CD45RA-depleted DLI were associated with improved recovery of CMV-specific T cells in CMV-seropositive recipients, though CMV viremia incidence did not differ. 34 A study comparing CD45RA-depleted vs CD3-depleted haplo-HSCT found improved T-cell reconstitution and reduced CMV and adenovirus viremia for CD45RA-depleted haplo-HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…The use of CD45RA-depleted T cells has also been studied in other transplantation protocols. 32 , 33 , 34 In a randomized trial of TCRαβ-depleted allogeneic HSCT, post-transplant CD45RA-depleted DLI were associated with improved recovery of CMV-specific T cells in CMV-seropositive recipients, though CMV viremia incidence did not differ. 34 A study comparing CD45RA-depleted vs CD3-depleted haplo-HSCT found improved T-cell reconstitution and reduced CMV and adenovirus viremia for CD45RA-depleted haplo-HSCT.…”
Section: Discussionmentioning
confidence: 99%